Zagadnienie ryzyka modelu w zarządzaniu ryzykiem - Kuziak, Katarzyna (Model Risk in Risk Management Process, 2005)
Model risk is understood as the special risk that arises when reality is described by theoretical model (every model is a simplification of reality). The first step before using any of theoretical models should be model risk control. Theoretical models play an important role in risk management process. Risk management process can be separated into three activities (steps): identification, measurement, monitor and control. In every step (for pricing, hedging, risk valuation) theoretical models will be used. This causes the additional risk, a so-called model risk. The paper will present model risk, types of model risk and sources of model risk. Empirical evidence will be given.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 119-125